Algebras of distributions suitable for phase‐space quantum mechanics. I - Gracia Bondía, José M. (1988)
The twisted product of functions on R^2N is extended to a *-algebra of tempered distributions which contains the rapidly decreasing smooth functions, the distributions of compact support, and all polynomials, and moreover is invariant under the Fourier transformation. The regularity properties of the twisted product are investigated. A matrix presentation of the twisted product is given, with respect to an appropriate orthonormal basis, which is used to construct a family of Banach algebras under this product.